Lower lymphocyte to monocyte ratio is a potential predictor of poor outcome in patients with cerebral venous sinus thrombosis - Li, Shen (Stroke Vasc Neurol, 2018)
BACKGROUND: Lymphocyte to monocyte ratio (LMR) is associated with functional outcome in patients with stroke. But the relationship between the LMR value and the prognosis of cerebral venous sinus thrombosis (CVST) has not been investigated. METHODS: CVST patients, admitted to the First Affiliated Hospital of Zhengzhou University, were retrospectively identified from November 2010 to January 2017. Functional outcomes of patients were evaluated with the modified Rankin Scale (mRS). Patients were divided into good (mRS 0–2) and poor (mRS 3–6) outcomes groups. Univariate and multivariate Cox regression analyses were used to assess the relationship between LMR and the poor survival outcome. RESULTS: A total of 228 patients were included of which 41 had poor outcomes (18.0%). The duration of follow-up was 22 months (6–66 months). LMR (2.3±1.2 vs 3.2±1.8, p<0.01) was significantly lower in the poor outcome group. Multivariate Cox regression analysis showed that LMR (HR 0.726, 95% CI 0.546 to 0.964, p=0.027) was a independent predictor of poor prognosis. CONCLUSIONS: LMR may be a predictor of poor prognosis in CVST patients.